Идея аренды в общественных начинаниях Льва Толстого 1857 г. [The Idea of Rent in Leo Tolstoy’s Social Enterprises of 1857] - Krasnoselskaia, Yulia (Slavica Revalensia, 2016)
In her article, Yulia Krasnosel’skaia demonstrates the correlation between Leo Tolstoy’s moral stance and his economic initiatives of 1857—such as Tolstoy’s plan to rent Nikolai Nekrasov’s Sovremennik, and his afforestation project, which was governed by the same idea. She emphasizes the fact that the idea of rent in these enterprises was prompted by Tolstoy’s practice as a landlord in 1856—58, thus placing Tolstoy’s idea of rent into a broader context.